Optimization of the Tax Ratio to Increase State Revenue Through the Tax Sector in Indonesia - Siti Rifqa Raihani; Khofifah Hasanah Pane; Irwan Triadi (Media Hukum Indonesia (MHI), 2026)
Taxes are the main source of state revenue and play an important role in supporting national development in Indonesia. However, Indonesia’s tax ratio is still relatively low compared to other countries, indicating that the potential for tax revenue has not been utilized optimally. This study aims to analyze the factors influencing the tax ratio and to formulate optimization strategies in order to increase state revenue through the tax sector. Efforts to optimize the tax ratio can be carried out through expanding the tax base, increasing taxpayer compliance, reforming tax policies, digitalizing administrative systems, and strengthening supervision and law enforcement. In addition, synergy between the government and society is also an important factor in creating an effective and sustainable tax system. The results of the study show that effective tax policies, including the expansion of the tax base, increased taxpayer compliance, and reform of tax administration, significantly contribute to increasing state revenue and improving the tax ratio. Therefore, comprehensive and sustainable tax optimization strategies are needed to improve state revenue performance and support fiscal stability